Molybdenum-tin-based catalyst and preparation method and application thereof
By using a molybdenum-tin-based catalyst preparation method, Sn-O-Sn, Mo-O-Sn, and Mo=O active centers are formed, solving the problems of high temperature, high energy consumption, and poor stability of existing catalysts. This method enables the low-temperature, highly selective oxidation of ethanol to acetaldehyde, and has good prospects for industrial application.
Patent Information
- Application Number
- CN202411526173.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
AI Technical Summary
Existing catalysts for the oxidation of ethanol to acetaldehyde suffer from problems such as high temperature and high energy consumption, short catalyst life and poor stability. In particular, Cu-based and Ag-based catalysts have insufficient activity at low temperatures, resulting in low ethanol conversion and selectivity.
Using a molybdenum-tin-based catalyst, by adjusting the heat treatment temperature of tin hydroxide, introducing the active component Mo and basic promoters, Sn-O-Sn, Mo-O-Sn, and Mo=O active centers are formed. This regulates the acidic centers on the catalyst surface, promotes the activation of Cα-H and OH bonds in ethanol, reduces the formation of byproducts, and achieves low-temperature, high-selectivity synthesis of acetaldehyde.
High ethanol conversion and acetaldehyde selectivity were achieved under normal pressure and low temperature conditions, significantly reducing reaction temperature and energy consumption, and improving catalyst stability, making it suitable for industrial applications.
Smart Images

Figure CN119259024A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a molybdenum-tin-based catalyst and a preparation method thereof and application thereof in ethanol oxidation to acetaldehyde, belonging to the technical field of catalyst preparation and application. Background Art
[0002] Acetaldehyde is an important organic chemical with the chemical formula CH3CHO. It is flammable and volatile, miscible with water and ethanol, and has strong reducing properties. Acetaldehyde is an important raw material for many chemicals and is widely used in the chemical, pharmaceutical, food and other industries. It has high industrial application value. Its downstream products, acetic acid, pyridine, acetate esters and other chemicals, can be further applied in different industries.
[0003] The main methods for synthesizing acetaldehyde include ethylene oxidation, acetylene hydration, acetic acid reduction, ethane oxidation, and ethanol oxidative dehydrogenation. At present, there are two main methods for synthesizing acetaldehyde in industry, ethylene oxidation and ethanol oxidative dehydrogenation. The catalyst used in the ethylene oxidation method is a solution composed of palladium chloride-copper chloride-hydrochloric acid-water, but this method has problems such as high catalyst cost, strong acid corrosion, and high equipment investment. Due to the large-scale production of biomass ethanol and the increase in coal-to-ethanol production capacity, its price is getting lower and lower, and the production of acetaldehyde from ethanol as raw material has become an important acetaldehyde synthesis route in industry. The ethanol dehydrogenation method not only has easy access to raw materials and low prices, but also has the advantages of good atom economy, environmental friendliness, and easy separation.
[0004] The production of acetaldehyde from ethanol is divided into direct dehydrogenation and oxidative dehydrogenation. Direct dehydrogenation has good atom economy, but due to the endothermic reaction, it is limited by thermodynamic equilibrium, the ethanol conversion rate is low, and the catalyst life is short. It has not yet been industrialized. Compared with the direct dehydrogenation method, the oxidative dehydrogenation process is an exothermic reaction, which overcomes the thermodynamic equilibrium limitation, greatly improves the reaction conversion rate, and has the advantages of a relatively stable catalyst and a long life. The ethanol oxidation method has been industrialized, using electrolytic silver as a catalyst. The reaction needs to be carried out at high temperature, and there are problems such as high energy consumption, high catalyst cost, and low ethanol conversion rate.
[0005] At present, there are two main methods for synthesizing acetaldehyde using ethanol as raw material, one is the direct dehydrogenation of ethanol to prepare acetaldehyde, and the other is the oxidative dehydrogenation of ethanol to prepare acetaldehyde. Chinese patent CN105148911A reported that carbon-supported Cu catalyst was used for direct dehydrogenation of ethanol to prepare acetaldehyde. The results showed that at a temperature of 180-300°C, the acetaldehyde selectivity was as high as 98.5%, but because the Cu particles were easy to migrate and agglomerate, the catalyst gradually deactivated and had poor stability. Chinese patent CN10673977A reported a Cu / carbon layer coated oxide composite catalyst for direct dehydrogenation of ethanol. The catalyst can inhibit the agglomeration of Cu components and improve the stability of the catalyst, but there are only 40h stability test results in the article. Chinese patent CN103880661A mentioned a Cu / SBA-15 catalyst for ethanol synthesis of acetaldehyde. At 260°C, the ethanol conversion rate was 45%, while the acetaldehyde selectivity was only 21%, and the by-product ethyl acetate selectivity was as high as 66%. Chinese patent CN110385139 A relates to a process for preparing acetaldehyde by direct dehydrogenation of ethanol. The catalyst loads Cu on a boron-containing compound carrier, achieving a catalyst preparation method with high ethanol conversion rate and high acetaldehyde selectivity. Similarly, the catalyst stability test is only 50 hours. The above-mentioned metal catalysts have a catalyst stability time of less than 50 hours. This is because the metal particles are prone to agglomeration and the catalyst is prone to deactivation, that is, the stability of this type of catalyst still needs to be further improved.
[0006] The main method for producing acetaldehyde from ethanol in industry is ethanol oxidation. The catalyst used is mainly electrolytic silver, silver mesh or pumice silver. The operating conditions of the catalyst are harsh, the reaction temperature is as high as 550°C, the high energy consumption and low efficiency caused by high temperature are obvious, and the catalyst cost is high and the life is short, and it needs to be replaced every 2 to 3 months. Chinese patent CN 118162155 A discloses a molybdenum-based catalyst for ethanol oxidation to acetaldehyde and its preparation method. The catalyst has the characteristics of significantly reducing the reaction temperature, and achieves the effect of efficient oxidation of ethanol to acetaldehyde at a temperature of 220°C and above, greatly reducing the reaction energy consumption, and the catalyst has a long service life. Compared with the industrial Ag method catalyst, although the catalyst has a significant reduction in the reaction temperature, the reaction is a violent exothermic reaction. If the reaction temperature can be further reduced and the ethanol injection amount can be increased, not only can the energy consumption be reduced, but also the acetaldehyde synthesis efficiency can be improved.
[0007] Therefore, it remains a challenge to develop a catalyst with a simple preparation method, good stability, and the ability to prepare acetaldehyde at lower temperatures and with higher selectivity. Summary of the invention
[0008] The present invention aims to provide a molybdenum-tin-based catalyst for ethanol oxidation to acetaldehyde and a preparation method thereof. The obtained catalyst is a catalyst with high activity, high selectivity, long life and suitable for low-temperature reaction, and can oxidize and dehydrogenate ethanol to prepare acetaldehyde under normal pressure and low temperature conditions.
[0009] The catalyst preparation method adopted by the present invention has a simple process and a large specific surface area of the prepared catalyst. In the synthesis process, by adjusting the heat treatment temperature of tin hydroxide, the surface of the tin hydroxide has structures such as Sn-OH and Sn-O-Sn, and the active component Mo and the alkaline auxiliary agent are further introduced. Sn-OH, as a functional group for anchoring the active component, can not only promote the dispersion of Mo, but also interact with the Mo precursor, so that the surface of the catalyst forms a surface interface with Sn-O-Sn, Mo-O-Sn, and Mo=O active centers, which not only greatly improves the mobility of lattice oxygen in metal oxygen species, but also provides a catalyst for the OH bond of ethanol and C α -H bond activation provides a variety of active sites. In addition, the introduction of an appropriate amount of alkaline additives not only regulates the strength and amount of acidic centers on the catalyst surface, reducing the production of by-products such as ether, ethyl acetate, and ethylene; at the same time, the alkaline additives also change the electronic environment of the Sn-O-Sn, Mo-O-Sn, and Mo=O structures, weakening the metal-oxygen bond and improving the mobility of lattice oxygen, especially the oxygen species in Mo=O, which can achieve C at a lower temperature. α The breaking of the -H bond (the rate-determining step of the reaction) enables the catalyst to catalyze the oxidation of ethanol to synthesize acetaldehyde with high selectivity at a relatively low temperature. In the metal catalysts in the prior art, the active metal is zero-valent (such as Cu), and its catalytic reaction is in the absence of oxygen. The active center of the present invention is a metal oxide, which is an aerobic dehydrogenation catalyst; in addition, the low-temperature oxidation activity of the Ag catalyst in the prior art is weak, and oxygen adsorption activation needs to be achieved at a higher temperature. Therefore, the low-temperature and high-performance molybdenum-tin-based catalyst mentioned in the present invention not only avoids the problem of catalyst deactivation caused by metal particle agglomeration, but is also more energy-efficient than the Ag catalyst, and can catalyze the oxidation of ethanol to acetaldehyde in the gas phase, at normal pressure, and at low temperature; in addition, compared with the Mo-based catalyst developed in the early stage, the catalyst developed in the present invention forms more Mo=O species, which is used in the oxidation of ethanol to acetaldehyde and has lower low-temperature oxidation performance.
[0010] The present invention provides a molybdenum-tin-based catalyst, which consists of two parts: an active metal oxide and an auxiliary metal oxide. Based on 100%, the weight percentage of the active metal oxide is 85-97%; the weight percentage of the auxiliary metal oxide is 3-15%.
[0011] The active metal oxides include MoO3 and SnO2; the weight ratio of MoO3 to SnO2 is 5-11:75-91. The catalyst product is prepared by an impregnation method, and the high content of Sn enables the tin oxide to better disperse the active metal and the auxiliary metal oxide, strengthens the interaction between the metal elements, and is conducive to the formation of more low-temperature oxidation centers Mo=O; on the other hand, the Sn-O-Sn exposed on the surface of the tin oxide is also conducive to the activation of ethanol.
[0012] The auxiliary metal oxide is one or two of ZrO2, MgO, Al2O3, CaO and K2O; wherein the weight ratio of ZrO2, MgO, Al2O3, CaO and K2O is 0-14.9:0-6.3:0-4.3:0-5.3:0-5.1.
[0013] The auxiliary oxide in the present invention is one or two of the above auxiliary metal oxides selected at random. Among them, MgO, CaO and K2O are used as alkaline auxiliary agents. According to their different alkalinity strengths, the alkaline centers on the catalyst surface are adjusted to promote the selective activation and bond breaking of OH and CH bonds in ethanol molecules. ZrO2, as an amphoteric oxide, can simultaneously adjust the acidic and alkaline centers on the catalyst surface. In the process of promoting the activation of OH and CH bonds, it can also suppress the byproducts (ethyl acetate, ethylene, etc.) produced by the strong acidity of the catalyst. The introduction of Al2O3 can increase the specific surface area and thermal stability of the catalyst, and can also adjust the acidity and alkalinity of the catalyst surface, thereby promoting the adsorption and activation of ethanol.
[0014] The present invention provides a method for preparing the above-mentioned molybdenum-tin-based catalyst, comprising the following steps: (1) Precipitation: dissolving a soluble tin salt in deionized water to prepare a solution with a tin ion concentration of 0.2-0.8 M, then adjusting the pH value of the solution to 8.0-10.0 with a precipitant, stirring at a rate of 700-2000 rpm, centrifuging the obtained alkaline suspension, washing to neutrality; drying at 70-120° C. for 8-15 hours, then raising the temperature to 120-250° C., and performing a heat treatment reaction for 6 hours to obtain a precipitate; (2) Impregnation: Soluble molybdenum salt and soluble auxiliary metal salt are dissolved in deionized water to prepare a mixed solution with a total metal ion concentration of 0.2~0.8M, wherein the molar ratio of Mo to auxiliary metal is 24.6~72.0:28.0~75.4; the precipitate is added to the prepared mixed solution, stirred for 30~60min at a stirring rate of 700~2000rpm, and rotary evaporated at 60~80℃ to a solid mixture, and then placed in an oven at 80~100℃ to dry for 6~12 hours; (3) Calcination: The sample obtained in step (2) is placed in a tubular furnace, heated to 400-600°C at a heating rate of 1-3°C per minute, and calcined for 6-12 hours, and then naturally cooled to room temperature to obtain the catalyst.
[0015] Furthermore, the precipitant is one of ammonia water, sodium nitrate and hydrochloric acid.
[0016] The soluble molybdenum salt is one of ammonium molybdate tetrahydrate and sodium molybdate dihydrate; the soluble tin salt is one of sodium stannate trihydrate, tin tetrachloride pentahydrate, stannous chloride dihydrate and stannous sulfate.
[0017] The soluble auxiliary metal salt is one or two of zirconium oxynitrate, magnesium nitrate hexahydrate, magnesium oxalate, aluminum nitrate, aluminum acetate, calcium chloride, potassium nitrate and potassium chloride.
[0018] The atmosphere during the calcination is one of oxygen and air.
[0019] The present invention provides application of the molybdenum-tin-based catalyst in ethanol oxidation to acetaldehyde.
[0020] The above application comprises the following steps: the ethanol oxidation reaction is carried out in a fixed bed reaction device, air or oxygen is mixed with ethanol vapor to form a reaction gas, the volume content of ethanol in the reaction gas is 5-15%, and the reaction gas space velocity is 5000-10000h -1 , the reaction temperature is 160~220℃, and the reaction pressure is 0.1~1.0MPa.
[0021] Beneficial effects of the present invention: (1) The present invention develops a method for preparing a catalyst for the high-selectivity production of acetaldehyde by oxidizing ethanol at low temperature. The designed molybdenum-tin-based catalyst forms a surface interface with Sn-O-Sn, Mo-O-Sn and Mo=O active centers, which is a catalyst for the production of acetaldehyde by ethanol C α -H bond and OH bond breaking and O2 adsorption activation provide specific spatial effects and active sites with different alkalinity levels. By introducing alkaline additives to regulate the strength and amount of acidic centers on the catalyst surface, the production of by-products such as ether, ethyl acetate, and ethylene is reduced, the low-temperature oxidation performance of the catalyst is significantly improved, and the catalytic oxidation of ethanol at relatively low temperatures is promoted to synthesize acetaldehyde with high selectivity; (2) Compared with the current silver catalysts in industry, this catalyst has the characteristic of significantly lowering the reaction temperature. Due to the use of a lower reaction temperature of 160~220℃, the generation of by-products is reduced. Within this temperature range, the ethanol conversion rate is 90%~100%, and the selectivity of acetaldehyde reaches 92%~99.6%; (3) The process of the present invention is simple, the reaction temperature is low, and it is carried out under normal pressure. In addition, the catalyst is easy to prepare, has good reproducibility, and has high selectivity for acetaldehyde. It is a green synthesis route with good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The Raman spectra of the catalyst of Example 6 of the present invention and the catalyst of Comparative Example 3 are shown. DETAILED DESCRIPTION
[0023] The present invention is further illustrated by the following examples, but is not limited to the following examples.
[0024] Comparative Example 1: The literature (Fuel 321 (2022) 123980) reported a Cu-based catalyst (Cu 1.4 / Zn x Mg 4.6-x Al2O 7.6 ) is used to catalyze the direct dehydrogenation of ethanol to produce acetaldehyde at 280 o C. At 0.1 MPa, the ethanol conversion rate was 64% and the acetaldehyde selectivity was 98%.
[0025] Comparative Example 2: The literature (Applied Catalysis A: General 528 (2016) 161–167) reported that an Ag-based catalyst (Ag-CeO2 / SiO2) was used to catalyze the oxidative dehydrogenation of ethanol to produce acetaldehyde at 190 o C, EtOH / O2 / He = 2 / 18 / 80, 60 ml / min, under normal pressure, the ethanol conversion rate is less than 90%, and the acetaldehyde selectivity is 98%.
[0026] Comparative Example 3: Chinese patent CN 118162155 A discloses a Mo-based catalyst for catalyzing the oxidative dehydrogenation of ethanol to produce acetaldehyde. o C, the ethanol conversion rate reached 97.3%, while the acetaldehyde selectivity remained at 95.9%. Example 1
[0027] 18.0 g SnCl2•2H2O was dissolved in deionized water to prepare a solution with a tin ion concentration of 0.2 mol / L. Then, the pH value of the solution was adjusted to 8.0 with sodium nitrate and the stirring rate was 700 rpm. The alkaline suspension was centrifuged and washed to neutrality. It was placed in a 70°C oven for drying for 8 hours, and then the temperature was raised to 120°C for heat treatment for 6 hours to obtain a precipitate. 1.2 g (NH4)6Mo7O 24•4H2O and 1.1g ZrO(NO3)2 are dissolved in deionized water to prepare a mixed solution with a total metal ion concentration of 0.2M; the precipitate obtained in the above step is added to the prepared mixed solution, stirred for 30min, the stirring rate is 700rpm, and the solid mixture is rotary evaporated at 60℃, and then placed in an 80℃ oven for 6 hours; the dried sample is placed in a tube furnace, heated to 400℃ at a heating rate of 1℃ per minute, calcined in air for 6 hours, and then naturally cooled to room temperature to obtain the catalyst. In terms of mass percentage, the contents of each component in the catalyst are: MoO3, 7.4%; SnO2, 88.2%; ZrO2, 4.4%.
[0028] The ethanol oxidation reaction is carried out in a fixed bed reactor. Air and ethanol vapor are mixed to form a reaction gas. The volume content of ethanol in the reaction gas is 5% and the reaction gas space velocity is 8000h -1 , the reaction temperature is 200℃, the reaction pressure is 0.1MPa. The reaction results are that the ethanol conversion rate is as high as 96.4%, and the acetaldehyde selectivity is 98.5%. Example 2
[0029] 32.6 g SnCl4•5H2O was dissolved in deionized water to prepare a solution with a tin ion concentration of 0.4 mol / L. The pH value of the solution was then adjusted to 8.0 with ammonia water and the stirring rate was 800 rpm. The alkaline suspension was centrifuged and washed to neutrality. It was placed in a 70°C oven for drying for 10 hours, and then the temperature was raised to 250°C for heat treatment for 6 hours to obtain a precipitate. 1.2 g (NH4)6Mo7O 24 •4H2O and 2.1g Al(NO3)3 are dissolved in deionized water to prepare a mixed solution with a total metal ion concentration of 0.4M; the precipitate obtained in the above step is added to the prepared mixed solution, stirred for 30min, the stirring rate is 800rpm, and the mixture is rotary evaporated at 60℃ to form a solid mixture, and then placed in an oven at 80℃ for 6 hours; the dried sample is placed in a tube furnace, heated to 500℃ at a heating rate of 2℃ per minute, calcined in air for 6 hours, and then naturally cooled to room temperature to obtain the catalyst. In terms of mass percentage, the contents of each component in the catalyst are: MoO3, 6.3%; SnO2, 87.5%; Al2O3, 6.2%.
[0030] The ethanol oxidation reaction is carried out in a fixed bed reactor. Air and ethanol vapor are mixed to form a reaction gas. The volume content of ethanol in the reaction gas is 6%, and the reaction gas space velocity is 6000h -1 , the reaction temperature is 220℃, the reaction pressure is 0.2MPa. The reaction results are that the ethanol conversion rate is as high as 100%, and the acetaldehyde selectivity is 95.9%. Example 3
[0031] 29.9 g SnCl2•2H2O was dissolved in deionized water to prepare a solution with a tin ion concentration of 0.6 mol / L. The pH value of the solution was then adjusted to 9.0 with sodium nitrate and the stirring rate was 900 rpm. The obtained alkaline suspension was centrifuged and washed to neutrality. It was placed in a 100°C oven for drying for 11 hours, and then the temperature was raised to 200°C for heat treatment for 6 hours to obtain a precipitate. 3.4 g Na2MoO4•2H2O and 2.1 g Al(NO3) 3 is dissolved in deionized water to prepare a mixed solution with a total metal ion concentration of 0.6M; the precipitate obtained in the above step is added to the prepared mixed solution, stirred for 50 minutes, the stirring rate is 900rpm, and the solid mixture is rotary evaporated at 65℃, and then placed in a 90℃ oven for 7 hours; the dried sample is placed in a tube furnace, heated to 400℃ at a heating rate of 1℃ per minute, calcined in oxygen for 10 hours, and then naturally cooled to room temperature to obtain the catalyst. In terms of mass percentage, the contents of each component in the catalyst are: MoO3, 8.7%; SnO2, 87.0%; Al2O3, 4.3%.
[0032] The ethanol oxidation reaction is carried out in a fixed bed reactor. Oxygen and ethanol vapor are mixed to form a reaction gas. The volume content of ethanol in the reaction gas is 10%, and the reaction gas space velocity is 10000h -1 , the reaction temperature is 200℃, the reaction pressure is 0.6MPa. The reaction results are that the ethanol conversion rate is as high as 97.6%, and the acetaldehyde selectivity is 99.5%. Example 4
[0033] 53.1 g of Na2SnO3·3H2O was dissolved in deionized water to prepare a solution with a tin ion concentration of 0.2 mol / L. The pH value of the solution was then adjusted to 10.0 with hydrochloric acid and the stirring rate was 1200 rpm. The alkaline suspension obtained was centrifuged and washed to neutrality. It was placed in an oven at 80°C for 12 hours and then heated to 150°C for 6 hours to obtain a precipitate. 3.4 g of Na2MoO4·2H2O and 3.5 g of CaCl2 Dissolve in deionized water to prepare a mixed solution with a total metal ion concentration of 0.5M; add the precipitate obtained in the above step to the prepared mixed solution, stir for 50 minutes, stir at a rate of 1200rpm, and evaporate at 65°C to form a solid mixture, then place in a 90°C oven for 9 hours; take the above dried sample and put it into a tube furnace, heat it to 600°C at a heating rate of 1°C per minute, roast it in oxygen for 10 hours, and then cool it naturally to room temperature to obtain the catalyst. In terms of mass percentage, the contents of each component in the catalyst are: MoO3, 5.9%; SnO2, 88.8%; CaO, 5.3%.
[0034] The ethanol oxidation reaction is carried out in a fixed bed reactor. Air and ethanol vapor are mixed to form a reaction gas. The volume content of ethanol in the reaction gas is 15%, and the reaction gas space velocity is 10000h -1 , the reaction temperature is 200℃, the reaction pressure is 0.4MPa. The reaction results are that the ethanol conversion rate is as high as 96.5%, and the acetaldehyde selectivity is 92.6%. Example 5
[0035] 49.9 g of SnSO4 was dissolved in deionized water to prepare a solution with a tin ion concentration of 0.8 mol / L. The pH value of the solution was then adjusted to 10.0 with ammonia water. The stirring rate was 2000 rpm. The alkaline suspension was centrifuged and washed to neutrality. It was placed in a 100°C oven for drying for 14 hours, and then the temperature was raised to 140°C for heat treatment for 6 hours. 3.1 g of (NH4)6Mo7O 24 •4H2O and 1.6g KCl are dissolved in deionized water to prepare a mixed solution with a total metal ion concentration of 0.7M; the precipitate obtained in the above step is added to the prepared mixed solution, stirred for 40min, the stirring rate is 2000rpm, and the solid mixture is rotary evaporated at 70℃, and then placed in a 100℃ oven for 7 hours; the dried sample is placed in a tube furnace, heated to 600℃ at a heating rate of 2℃ per minute, calcined in air for 12 hours, and then naturally cooled to room temperature to obtain the catalyst. In terms of mass percentage, the contents of each component in the catalyst are: MoO3, 6.3%; SnO2, 88.6%; K2O, 5.1%.
[0036] The ethanol oxidation reaction is carried out in a fixed bed reactor. Oxygen and ethanol vapor are mixed to form a reaction gas. The volume content of ethanol in the reaction gas is 8%, and the reaction gas space velocity is 9000h -1 , the reaction temperature is 160℃, the reaction pressure is 0.1MPa. The reaction results are that the ethanol conversion rate is as high as 90.0%, and the acetaldehyde selectivity is 99.6%. Example 6
[0037] 23.3 g SnCl4•5H2O was dissolved in deionized water to prepare a solution with a tin ion concentration of 0.5 mol / L. The pH value of the solution was then adjusted to 9.0 with ammonia water and the stirring rate was 1000 rpm. The obtained alkaline suspension was centrifuged and washed to neutrality. It was placed in an oven at 110°C for 15 hours and then heated to 220°C for 6 hours to obtain a precipitate. 1.2 g (NH4)6Mo7O 24 •4H2O, 3.2g Mg(NO3)2•6H2O and 1.0g CaCl2 are dissolved in deionized water to prepare a mixed solution with a total metal ion concentration of 0.8M; the precipitate obtained in the above step is added to the prepared mixed solution, stirred for 40min, the stirring rate is 1000rpm, and the solid mixture is rotary evaporated at 70℃, and then placed in a 100℃ oven for 8 hours; the dried sample is placed in a tube furnace, heated to 400℃ at a heating rate of 3℃ per minute, calcined in air for 9 hours, and then naturally cooled to room temperature to obtain the catalyst. In terms of mass percentage, the contents of each component in the catalyst are: MoO3, 8.3%; SnO2, 83.3%; MgO, 4.2%; CaO, 4.2%.
[0038] The ethanol oxidation reaction is carried out in a fixed bed reactor. Air and ethanol vapor are mixed to form a reaction gas. The volume content of ethanol in the reaction gas is 5%, and the reaction gas space velocity is 7000h -1 , the reaction temperature was 210°C, the reaction pressure was 0.1MPa. The reaction results showed that the ethanol conversion rate was as high as 95.8%, and the acetaldehyde selectivity was 96.7%.
[0039] Figure 1 Figure 2 is a Raman spectrum of the catalyst of Example 6 of the present invention and the catalyst of Comparative Example 3. Figure 1 It can be seen that compared with the catalyst of Comparative Example 3, the characteristic peak attributed to the Mo=O bond in the catalyst of the present invention is at a lower wave number, indicating that the characteristic peak of the Mo=O bond has undergone a red shift, its bond energy is reduced, and bond breaking is prone to occur, and the C in the ethanol molecule can be activated at a lower temperature (210°C). α-H bond (rate-determining step), promoting ethanol conversion. Obviously, the catalyst developed by the present invention can show higher acetaldehyde synthesis performance at a lower temperature.
[0040] The catalyst reaction temperature in Comparative Example 3 was 270 At 140 °C, the ethanol conversion rate reached 97.3%, and the acetaldehyde selectivity remained at 95.9%; in contrast, the reaction temperature of this embodiment reached 210 °C, and the catalysts in Examples 1 to 10 of the present invention achieved excellent catalytic effects at a reaction temperature of 160 to 220 °C, that is, the catalytic reaction was achieved at a lower temperature. Experiments show that the technology of the present invention significantly improves the low-temperature oxidation performance of the catalyst. Example 7
[0041] 21.2 g of Na2SnO3·3H2O was dissolved in deionized water to prepare a solution with a tin ion concentration of 0.8 mol / L. The pH value of the solution was then adjusted to 9.0 with hydrochloric acid and the stirring rate was 1500 rpm. The obtained alkaline suspension was centrifuged and washed to neutrality. It was placed in an oven at 80°C for 10 hours and then heated to 190°C for 6 hours to obtain a precipitate. 1.8 g of (NH4)6Mo7O 24 •4H2O and 0.9g ZrO(NO3)2 are dissolved in deionized water to prepare a mixed solution with a total metal ion concentration of 0.3M; the precipitate obtained in the above step is added to the prepared mixed solution, stirred for 60min, the stirring rate is 1500rpm, and the solid mixture is rotary evaporated at 75℃, and then placed in a 90℃ oven for 8 hours; the dried sample is placed in a tube furnace, heated to 500℃ at a heating rate of 2℃ per minute, calcined in oxygen for 12 hours, and then naturally cooled to room temperature to obtain the catalyst. In terms of mass percentage, the contents of each component in the catalyst are: MoO3, 10.7%; SnO2, 85.7%; ZrO2, 3.6%.
[0042] The ethanol oxidation reaction is carried out in a fixed bed reactor. Air and ethanol vapor are mixed to form a reaction gas. The volume content of ethanol in the reaction gas is 5%, and the reaction gas space velocity is 8000h -1 , the reaction temperature is 170℃, the reaction pressure is 1.0MPa. The reaction results are that the ethanol conversion rate is as high as 97.5%, and the acetaldehyde selectivity is 94.8%. Example 8
[0043] 67.4 g SnCl2•2H2O was dissolved in deionized water to prepare a solution with a tin ion concentration of 0.2 mol / L. The pH value of the solution was then adjusted to 10.0 with sodium nitrate and the stirring rate was 1000 rpm. The obtained alkaline suspension was centrifuged and washed to neutrality. It was placed in a 120°C oven for drying for 9 hours, and then the temperature was raised to 240°C for heat treatment for 6 hours to obtain a precipitate. 5.0 g Na2MoO4•2H2O, 3.7 g MgC2O4•2H2O and 0. 5 grams of KNO3 are dissolved in deionized water to prepare a mixed solution with a total metal ion concentration of 0.4M; the precipitate obtained in the above step is added to the prepared mixed solution, stirred for 60 minutes, the stirring rate is 1000rpm, and the solid mixture is rotary evaporated at 75℃, and then placed in an oven at 80℃ for 10 hours; the dried sample is placed in a tube furnace, heated to 600℃ at a heating rate of 3℃ per minute, calcined in air for 10 hours, and then naturally cooled to room temperature to obtain the catalyst. In terms of mass percentage, the contents of each component in the catalyst are: MoO3, 6.1%; SnO2, 90.9%; MgO, 4.4%; K2O, 1.0%.
[0044] The ethanol oxidation reaction is carried out in a fixed bed reactor. Air and ethanol vapor are mixed to form a reaction gas. The volume content of ethanol in the reaction gas is 10%, and the reaction gas space velocity is 5000h -1 , the reaction temperature is 190℃, the reaction pressure is 1.0MPa. The reaction results are that the ethanol conversion rate is as high as 93.5%, and the acetaldehyde selectivity is 95.7%. Example 9
[0045] 16.3 g SnCl4•5H2O was dissolved in deionized water to prepare a solution with a tin ion concentration of 0.6 mol / L. The pH value of the solution was then adjusted to 8.0 with ammonia water. The stirring rate was 1600 rpm. The alkaline suspension was centrifuged and washed to neutrality. It was placed in a 120°C oven for drying for 8 hours, and then the temperature was raised to 140°C for heat treatment for 6 hours to obtain a precipitate. 1.7 g Na2MoO4•2H2O and 2.6 g ZrO(NO3)2 Dissolve in deionized water to prepare a mixed solution with a total metal ion concentration of 0.5M; add the precipitate obtained in the above step to the prepared mixed solution, stir for 30 minutes, stir at a rate of 1600rpm, and evaporate at 80℃ to form a solid mixture, then place in an oven at 80℃ for 12 hours; take the dried sample and put it into a tube furnace, heat it to 400℃ at a heating rate of 1℃ per minute, roast it in air for 6 hours, and then cool it naturally to room temperature to obtain the catalyst. In terms of mass percentage, the contents of each component in the catalyst are: MoO3, 10.6%; SnO2, 74.5%; ZrO2, 14.9%.
[0046] The ethanol oxidation reaction is carried out in a fixed bed reactor. Oxygen and ethanol vapor are mixed to form a reaction gas. The volume content of ethanol in the reaction gas is 6%, and the reaction gas space velocity is 10000h -1 , the reaction temperature is 210℃, the reaction pressure is 0.2MPa. The reaction results are that the ethanol conversion rate is as high as 94.8%, and the acetaldehyde selectivity is 99.2%. Example 10
[0047] 64.1 g of SnSO4 was dissolved in deionized water to prepare a solution with a tin ion concentration of 0.7 mol / L, and then the pH value of the solution was adjusted to 8.0 with ammonia water, and the stirring rate was 900 rpm. The obtained alkaline suspension was centrifuged and washed to neutrality; it was placed in a 100°C oven for drying for 15 hours, and then the temperature was increased to 210°C and heat-treated for 6 hours to obtain a precipitate; 4.2 g of Na2MoO4•2H2O and 3.6 g of (CH3COO)3Al were dissolved in deionized water to prepare a mixed solution with a total metal ion concentration of 0.3 M; the precipitate obtained in the above steps was added to the prepared mixed solution, stirred for 40 minutes, the stirring rate was 900 rpm, and rotary evaporated at 80°C to form a solid mixture, and then placed in a 100°C oven for drying for 11 hours; the above dried sample was taken and placed in a tubular furnace, and the temperature was increased to 600°C at a heating rate of 2°C per minute, and it was roasted in air for 8 hours, and then naturally cooled to room temperature to obtain the catalyst. In terms of mass percentage, the contents of each component in the catalyst are: MoO3, 5.1%; SnO2, 91.3%; Al2O3, 3.7%.
[0048] The ethanol oxidation reaction is carried out in a fixed bed reactor. Oxygen and ethanol vapor are mixed to form a reaction gas. The volume content of ethanol in the reaction gas is 8%, and the reaction gas space velocity is 8000h -1 , the reaction temperature was 220°C, the reaction pressure was 0.4MPa. The reaction results showed that the ethanol conversion rate was as high as 95.7%, and the acetaldehyde selectivity was 92.0%. Embodiment 11
[0049] The catalyst prepared in Example 6 was used for the stability test reaction of ethanol oxidation to produce acetaldehyde. The reaction was carried out in a fixed bed reactor. Oxygen and ethanol vapor were mixed to form a reaction gas. The volume content of ethanol in the reaction gas was 5%. The reaction gas space velocity was 7000 h -1 , the reaction temperature was 210℃, and the reaction pressure was 0.1MPa. During the 150 h test, the catalyst maintained good stability without obvious deactivation, the ethanol conversion rate was maintained at about 96.0%, and the acetaldehyde selectivity was maintained at about 97.0%.
Claims
1. A molybdenum-tin-based catalyst, characterized in that: It consists of two parts: active metal oxide and auxiliary metal oxide, wherein the weight percentage of active metal oxide is 85-97%, and the weight percentage of auxiliary metal oxide is 3-15%; the active metal oxide includes MoO3 and SnO2; the weight ratio of MoO3 to SnO2 is 5-11:75-91.
2. The molybdenum-tin-based catalyst according to claim 1, characterized in that: The auxiliary metal oxide is one or two of ZrO2, MgO, Al2O3, CaO and K2O; wherein the weight ratio of ZrO2, MgO, Al2O3, CaO and K2O is 0-14.9:0-6.3:0-4.3:0-5.3:0-5.
1.
3. A method for preparing a molybdenum-tin-based catalyst according to claim 1 or 2, characterized in that The following steps are involved: (1) Precipitation: dissolving a soluble tin salt in deionized water to prepare a solution with a tin ion concentration of 0.2-0.8 M, then adjusting the pH value of the solution to 8.0-10.0 with a precipitant, stirring at a rate of 700-2000 rpm, centrifuging the obtained alkaline suspension, washing to neutrality; drying at 70-120° C. for 8-15 hours, then raising the temperature to 120-250° C., and performing a heat treatment reaction for 6 hours to obtain a precipitate; (2) Impregnation: Soluble molybdenum salt and soluble auxiliary metal salt are dissolved in deionized water to prepare a mixed solution with a total metal ion concentration of 0.2-0.8 M; the precipitate is added to the prepared mixed solution, stirred for 30-60 min at a stirring rate of 700-2000 rpm, and rotary evaporated at 60-80 ° C to form a solid mixture, which is then placed in an oven at 80-100 ° C to dry for 6-12 hours; (3) Calcination: The sample obtained in step (2) is placed in a tubular furnace, heated to 400-600°C at a heating rate of 1-3°C per minute, and calcined for 6-12 hours, and then naturally cooled to room temperature to obtain a molybdenum-tin-based catalyst.
4. The method for preparing a platinum-tin-based catalyst according to claim 3, characterized in that: The precipitant is one of ammonia water, sodium nitrate and hydrochloric acid.
5. The method for preparing a platinum-tin-based catalyst according to claim 3, characterized in that: The soluble molybdenum salt is one of ammonium molybdate tetrahydrate and sodium molybdate dihydrate; the soluble tin salt is one of sodium stannate trihydrate, tin tetrachloride pentahydrate, stannous chloride dihydrate and stannous sulfate.
6. The method for preparing a platinum-tin-based catalyst according to claim 3, characterized in that: The soluble auxiliary metal salt is one or two of zirconium oxynitrate, magnesium nitrate hexahydrate, magnesium oxalate, aluminum nitrate, aluminum acetate, calcium chloride, potassium nitrate and potassium chloride.
7. The method for preparing a platinum-tin-based catalyst according to claim 3, characterized in that: In the mixed solution prepared in step (2), the molar ratio of Mo metal to auxiliary metal is 24.6-72.0:28.0-75.
4.
8. The method for preparing a platinum-tin-based catalyst according to claim 3, characterized in that: The atmosphere during calcination is one of oxygen and air.
9. Use of the molybdenum-tin-based catalyst according to claim 1 or 2 in ethanol oxidation to produce acetaldehyde.
10. The use according to claim 9, characterized in that: The ethanol oxidation reaction is carried out in a fixed bed reactor. Air or oxygen is mixed with ethanol vapor to form a reaction gas. The volume content of ethanol in the reaction gas is 5-15%, and the reaction gas space velocity is 5000-10000h -1 , the reaction temperature is 160~220℃, and the reaction pressure is 0.1~1.0MPa.
Citation Information
Patent Citations
Shell catalyst, its use for oxidizing methanol to formaldehyde and its process of preparation
CN101340975A
Catalyst for formaldehyde preparation by methanol oxidation and preparation method of catalyst
CN107952445A
Molybdenum-based catalyst for preparing acetaldehyde through ethanol oxidation and preparation method of molybdenum-based catalyst
CN118162155A
Method for producing alcohol and / or ketone
CN1918093A